The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1097/sla.0b013e31816c401d
|View full text |Cite
|
Sign up to set email alerts
|

Does Reported Funding Differ by Gender in the Surgical Literature?

Abstract: The percentage of original surgical articles first authored by women is greater than the percentage of female surgeons. Funding rates of original articles were similar among men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
2
10
1
Order By: Relevance
“…It may be due to fewer female surgeons, or differences in career success and/or academic productivity between genders. Moreover, most surgical residents, surgeons, research leaders and departmental chairs in the USA, and editorial board members in top ranked surgical journals are male (Kurichi et al, 2005;Taira et al, 2008). However, our study could not identify a reason for the authorship inequality.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…It may be due to fewer female surgeons, or differences in career success and/or academic productivity between genders. Moreover, most surgical residents, surgeons, research leaders and departmental chairs in the USA, and editorial board members in top ranked surgical journals are male (Kurichi et al, 2005;Taira et al, 2008). However, our study could not identify a reason for the authorship inequality.…”
Section: Discussioncontrasting
confidence: 55%
“…The gender gap in authorship still exists as evidenced by our observation and others studies (Kurichi et al, 2005;Taira et al, 2008). The number of women first authors in surgical literature remains low, despite increasing over time.…”
Section: Discussionmentioning
confidence: 47%
“…Firstly, females might develop fewer publications than male colleagues. However, the gender difference in publication productivity is still highly controversial in US (Schroen et al 2004;Housri et al 2008;Taira et al 2008), and we need to evaluate the gender difference in publication by Japanese surgeons. The second possible reason is sexual and gender discrimination or harassment.…”
Section: Discussionmentioning
confidence: 99%
“…Timeline analysis since 2004, when gender data were first recorded, showed a yearly increase in the number and proportion of female clinical academics in UK medical schools (Medical Schools Council 2012). The other bulk of research on gender gap in academic medicine was based on these databases (Bickel et al 2002;Jagsi et al 2006;Kass et al 2006;Taira et al 2008;Ahmadiyeh et al 2010;Isaac et al 2010;Zhuge et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric studies have reported on methodologies and evidence base using research design hierarchies (Papatheodorou et al 2008;Rochon et al 2004); recognised recommendations (Yoshii et al 2009), and grading systems (Brooke et al 2009;Moseley et al 2002). Collaboration has been quantified using the number of authors (Levsky et al 2007;Papatheodorou et al 2008), gender (Jagsi et al 2006), qualification (Taira et al 2008), affiliation (Andres Iglesias et al 2007, Coleman et al 2007Hendrix 2008;Richter et al 2008;Williams and Kendall 2007) and geographical location of authors (Clarke et al 2007;Garcia-Garcia et al 2008;Yang and Zhao 2008;Gonzalez Block 2006;Soteriades et al 2005). These indices, rather than assessing consumer demand, provide descriptive data on the product (research outputs) and the process of knowledge production.…”
Section: Introductionmentioning
confidence: 98%